Building Character Values Through Cooperative Learning in Choir Activities: Evidence from Longitudinal Action Research - Dhea Elvionita Surya; Tati Narawati; Agus Budiman (Journal of Innovation and Research in Primary Education, 2026)
Choir activities in higher education predominantly emphasize technical musical aspects while overlooking their potential as comprehensive character education platforms. This study addresses the knowledge gap regarding specific mechanisms through which structured collaborative learning transforms character values in university choir contexts. This two-year qualitative action research employed Cooperative Learning interventions in student choir activities at IAKN Palangka Raya, Indonesia. Seven focal students exhibiting problematic behaviors were selected from 30 choir members. Data were collected through participatory observation, in-depth interviews, and documentation across two intervention cycles, then analyzed using qualitative descriptive methods with triangulation for validity. The systematic implementation of Cooperative Learning through small group practice, peer teaching, leadership rotation, and structured reflection successfully transformed student character values. Focal students progressed from chronic tardiness, minimal engagement, and individualistic attitudes to demonstrating sustained discipline (95%+ attendance), personal responsibility, cooperative commitment, and empathetic awareness. Musical competence improved concurrently, culminating in competitive achievements at city, provincial, and national levels. A novel finding revealed that character development temporally preceded musical improvement by 3-4 weeks, suggesting character values function as foundational infrastructure enabling optimal artistic learning. Cooperative Learning effectively cultivates multidimensional character development alongside musical competence in higher education choir settings. The findings position structured collaborative pedagogy as essential for realizing choir activities' full potential as holistic character education spaces.